The Nanda Devi Biosphere Reserve : Programme on Man and the Biosphere (MAB) (Indian National Man and the Biosphere Committee, Dept. of Environment, 1984)
Ecology of the reserve forests in the Garhwal Himalayas, Uttar Pradesh.